The Association of Polycystic Ovary Syndrome and Gestational Hypertensive Disorders in a Diverse Community-Based Cohort - Diane Schneider; Joel R. Gonzalez; Miya Yamamoto; Jingrong Yang; Joan C. Lo (Hindawi Limited, 2019)
Purpose. To examine the association of polycystic ovary syndrome (PCOS) and pregnancy-induced hypertension (PIH) within a large population of pregnant women in an integrated healthcare system. Methods. This retrospective study utilized a source cohort of 1023 women with PCOS and 1023 women without PCOS who had a delivered pregnancy within Kaiser Permanente Northern California. Preexisting hypertension was defined by hypertension diagnosis, treatment, or elevated blood pressure prior to 20 weeks of gestation. The development of PIH, including gestational hypertension, preeclampsia/eclampsia, or HELLP (hemolysis, elevated liver enzymes, and low platelet count), was ascertained by chart review. Among women without preexisting hypertension who had a singleton pregnancy, the association of PCOS and PIH was examined using multivariable logistic regression. Results. Among 1902 women (910 PCOS) with singleton pregnancy, 101 (11.1%) PCOS and 36 (3.6%) non-PCOS women had preexisting hypertension and were excluded. Of the remaining 1765 women, those with PCOS (compared to non-PCOS) were slightly older (mean age 31.2 versus 30.7), more likely to be obese (39.6% versus 15.1%), nulliparous (63.8% versus 43.4%), and conceive with fertility treatment (54.1% versus 1.9%); they also had a higher incidence of PIH (10.8% versus 6.6%), including gestational hypertension (5.8% versus 3.6%) and preeclampsia or HELLP (4.9% versus 3.0%; all p<0.05). PCOS was associated with increased odds of PIH (odds ratio, OR 1.7, 95% confidence interval, CI 1.2-2.4), remaining significant after adjusting for age, race/ethnicity, nulliparity, and fertility treatment; however, findings were attenuated and no longer significant after adjusting for weight status (OR 1.1, CI 0.7-1.7). Maternal PCOS was also associated with preeclampsia/HELLP in unadjusted but not adjusted (OR 1.0, CI 0.5-1.9) analyses. Nulliparity and higher prepregnancy BMI were associated with PIH in both groups. Conclusion. Compared to women without PCOS, women with PCOS are at higher risk for PIH but this association was not independent of weight status.